BRIDGING TRADITIONS AND TECHNOLOGY: DIGITAL TRANSFORMATION IN INDONESIAN ISLAMIC BOARDING SCHOOLS (GONTOR AND LIRBOYO) - Nurwahidin; Mohammad Izdiyan Mutaqin; S Salahudin Suyurno (Journal of Islamic, Social, Economics and Development, 2023)
Simultaneously with the emergence of the COVID-19 pandemic, educational institutions in the form of Islamic boarding schools led by Kiai (Moslem Scholar) continued to carry out the learning process with various adaptations and adjustments. This research was conducted to reveal the digital transformation that has occurred in Islamic boarding schools, as well as the changes made by these schools to adapt to changes in the digital era while continuing to carry out the important duties of Islamic boarding schools in Indonesian society, namely, to maintain the spirituality and morality of society. The challenges and vision of the institutions in dealing with digital transformation are also studied. This research is qualitative; the data were obtained through interviews and observations at several institutions, namely Pondok Modern Darussalam Gontor, and Pondok Pesantren Lirboyo. This research reveals that Islamic boarding schools and have made various efforts to carry out digital transformation while continuing to carry out several restrictions to prevent misuse of digital technology for things that are contrary to Islamic teachings.